Studying the relationship between mTOR activity and fertility hormones imbalances in polycystic ovary syndrome in Basra city - moslim, Asmaa; Mohammed Hadi, Ali; Waleed, Nisreen (University of Thi-Qar Journal of Science, 2025)
Polycysticovariansyndrome (PCOS) is an endocrine-related condition that is world’s leading cause of infertility affects women of reproductive age. The current study set out to investigate the effect of mTOR functions on PCOS women and its relation to fertility hormones. Total of 62 blood samples were collected, 42 of them were gathered from those who had recently been diagnosed with PCOS and 20 samples were collected from healthy women. The levels of mammalian target of rapamycin (mTOR) were measured using the (ELISA) technique while prolactin and testosterone were measured by Cobas e411. The study found a significant decrease in mTOR levels and a significant increase in prolactin and testosterone levels in women with PCOS compared to healthy women. Regarding age and BMI groups, no discernible variations were detected. This study concluded that dysregulation of mTOR is linked with PCOS, in addition, mTOR has a negative relationship with prolactin.